Birnam Wood - Catton, Eleanor 1985- (Granta, 2023)
"The Booker-winning author of The Luminaries delivers a gripping thriller of high drama and kaleidoscopic insight into what drives us to survive"--
Keywords: Thrillers (Fiction); Novels